Contraction with Unpacking: When Unpacking Leads to Lower Calorie Budgets - Jia, Miaolei (Liam); Li, Xiuping; Krishna, Aradhna (Journal of Consumer Research, 2020)
Abstract Consumers set a lower consumption budget when they set individual calorie budgets for constituent categories (e.g., breakfast, lunch, dinner, and snacks; categorical approach) versus when they set a total budget (overall approach). This contraction effect of unpacking a judgment is driven by motivated reasoning. Consumers are motivated to reduce calorie consumption, and this motive directs their cognitive elaboration for the budget decision to be on what to cut and how much to cut. Furthermore, the categorical (vs. overall) approach brings to mind more thoughts that are consistent with the motive to reduce consumption, which then leads to a lower calorie budget. Consistent with this explanation, the level of elaboration on reducing calorie intake—especially on occasions where overconsumption is less salient—mediates the contraction effect. In addition, the contraction effect is attenuated when the motive to reduce consumption is deactivated. Finally, while the contraction effect occurs when consumers have a motive to reduce consumption, the classic expansion effect of unpacking occurs when consumers are prompted to think about what to consume or are motivated to increase consumption. The results for calorie budgeting are shown to have downstream consequences on actual food consumption.